Top 10 Downloads from ACM's Digital Library. (Communications of the ACM, 2005)
The article presents a list of papers, courses and magazines downloaded, in July 2005, from the Association of Computing Machinery's digital library. Some of the papers that were downloaded are: "Architectures for a Temporal Workflow Management System," by Carlo Combi, Giuseppe Pozzi and published in the March 2004 issue of the journal "Proceedings of the 2004 ACM Symposium on Applied Computing"; and "The Google File System," by Sanjay Ghemawat, Howard Gobioff and Shun-Tak Leung and published in the October 2003 issue of the journal "Proceedings of the 19th ACM Symposium on Operating Systems Principles." Some of the courses that were downloaded are: Introduction to the Java Programming Language; UML Fundamentals; Data Modeling; Beginning to Program With the Java Programming Language; Project Management: Initiation and Plan Launch; and Basic Programming in C.